Secondary batteries and electronic devices
By using mixed silicon carbon particles and regulating electrolyte components in the negative electrode material layer of the secondary battery, the thermal stability and capacity maintenance problems of high-energy-density secondary batteries under high temperature and fast charging cycles are solved, and higher energy density and lower capacity loss are achieved.
Patent Information
- Application Number
- CN202411827604.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The temperature of the high-energy-density secondary batteries rises rapidly in high-temperature environments, affecting battery performance and safety. The rapid charging and discharging leads to uneven electrochemical reactions, resulting in a sharp attenuation of capacity.
By using silicon carbon particles of large and small particle sizes in the negative electrode material layer of the secondary battery, and controlling their particle number and electrolyte components, an appropriate pore structure is formed to buffer expansion and contraction during charging and discharging.
Under the premise of high energy density, the thermal stability of the secondary battery and the capacity maintenance after fast charging cycle are improved, and the capacity loss rate is reduced.
Smart Images

Figure SMS_3 
Figure SMS_4 
Figure SMS_5
Abstract
Description
Technical Field
[0001] The present application belongs to the field of energy storage technology, and specifically relates to a secondary battery and an electronic device. Background Art
[0002] As a rechargeable battery, secondary batteries can store and release energy through the transfer of electrons between the positive and negative electrodes. They have the advantages of safety, portability, and long life, and are therefore widely used in mobile devices, electric vehicles, and other fields. Among them, high-energy-density secondary batteries can store more energy within a limited volume or weight, which is crucial to improving the endurance of electronic devices.
[0003] However, when the energy density of secondary batteries increases, it means that at the same volume or weight, more chemical energy is stored or released inside during the charge and discharge process. In a high temperature environment, the temperature of high energy density secondary batteries rises faster, which affects battery performance and safety, and even causes serious problems such as thermal runaway. And under fast charge and discharge conditions, large currents can easily lead to uneven electrochemical reactions inside the battery, causing the capacity of the secondary battery to decay sharply. Therefore, how to improve the thermal stability and fast charge cycle performance of secondary batteries is a technical problem that needs to be solved urgently. Summary of the invention
[0004] The purpose of the present application is to provide a secondary battery and an electronic device, which can achieve a higher energy density while improving the thermal stability of the secondary battery and reducing the capacity loss rate after fast charging cycles.
[0005] In the first aspect, the present application provides a secondary battery. The secondary battery comprises a positive electrode, a negative electrode and an electrolyte, the negative electrode comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, the negative electrode material layer comprises silicon-carbon particles, and the particle size of the silicon-carbon particles is R µm. The silicon-carbon particles comprise first silicon-carbon particles and second silicon-carbon particles, when 2.5≤R≤13, the silicon-carbon particles are first silicon-carbon particles, and the number of particles of the first silicon-carbon particles is N1, when 0.1≤R≤2, the silicon-carbon particles are second silicon-carbon particles, and the number of particles of the second silicon-carbon particles is N2, and the negative electrode material layer satisfies: 5≤N2 / N1≤30. The secondary battery provided in the present application, while achieving a higher energy density, takes into account improving the thermal stability of the secondary battery after a fast charge cycle and reducing the capacity loss rate of the fast charge cycle.
[0006] Without being limited to any theory, the inventors of the present application have found that although mixing large-size silicon-carbon particles with small-size silicon-carbon particles can increase the compaction density of the negative electrode sheet and further increase the volume energy density of the secondary battery, the thermal stability of the secondary battery and the capacity retention after fast charge cycles will be significantly deteriorated. The present application adjusts the number of the first silicon-carbon particles and the second silicon-carbon particles to satisfy the above relationship, thereby achieving a higher energy density while taking into account improving the thermal stability of the secondary battery after fast charge cycles and reducing the capacity loss rate of fast charge cycles.
[0007] The inventor speculates that the shrinkage and expansion degree of large-sized silicon-carbon particles and small-sized silicon-carbon particles when deintercalating lithium are different, and the shrinkage and expansion space required is also different. When the negative electrode material in the negative electrode material layer containing the above silicon-carbon particles is too dense, it is easy to cause the problem of uneven force on the negative electrode material. The material pulverization and conductive network disconnection caused by uneven force are more obvious after fast charging cycles, resulting in the deterioration of the thermal stability of the battery after fast charging cycles, and the increase of capacity loss caused by fast charging cycles. By controlling the ratio N2 / N1 of the number of silicon-carbon particles N1 with a particle size of 2.5µm to 13µm and the number of silicon-carbon particles N2 with a particle size of 0.1µm to 2µm to satisfy 5≤N2 / N1≤30, the stacking state of silicon-carbon particles in the negative electrode sheet can be adjusted, so that large-size silicon-carbon particles and small-size silicon-carbon particles form a uniform stack in the negative electrode material layer, and pores with appropriate volumes are formed between the stacks, providing a suitable buffer space for the expansion and contraction of silicon-carbon particles during the charge and discharge process. The appropriate volume of pores means that the silicon-carbon particles will not be accelerated to pulverize due to serious uneven force after expansion due to excessive pores, nor will the conductive network of silicon-carbon particles be broken after contraction due to excessively small pores, thereby further reducing the degree of deterioration of battery performance caused by fast charging cycles. When adjacent large-size silicon-carbon particles are stacked, pores are formed. The present application uses an appropriate number of small-size silicon-carbon particles to fill the pores between the large-size silicon-carbon particles. This can not only form a sufficient conductive network in the negative electrode material layer, but also avoid an overly dense stacking state that causes the silicon-carbon particles to accelerate pulverization during expansion and contraction, further reducing the possibility of deterioration of thermal stability and increased capacity loss due to pulverization, and balancing the difference in shrinkage and expansion space between 2.5µm to 13µm silicon-carbon particles and 0.1µm to 2µm silicon-carbon particles. While achieving a higher energy density, it also takes into account improving the thermal stability of the secondary battery after a fast-charge cycle and reducing the capacity loss of the fast-charge cycle.
[0008] In some embodiments, 10≤N2 / N1≤25. By adjusting the value of N2 / N1 within the above range, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of fast charge cycle can be reduced.
[0009] In some embodiments, the electrolyte contains ethylene carbonate and propylene carbonate, and based on the mass of the electrolyte, the mass percentage of ethylene carbonate is E%, and the mass percentage of propylene carbonate is P%, and 2≤E / P≤8. By making the electrolyte contain both ethylene carbonate and propylene carbonate and adjusting the value of E / P within the above range, it is helpful to simultaneously form a solid electrolyte interface film of appropriate thickness on the surface of the first silicon-carbon particles and the surface of the second silicon-carbon particles, thereby further improving the thermal stability of the secondary battery after fast charge cycles and reducing the capacity loss of fast charge cycles.
[0010] In some embodiments, 2.5≤E / P≤6. By adjusting the value of E / P within the above range, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of fast charge cycle can be reduced.
[0011] In some embodiments, 20≤E≤36. By adjusting the value of E within the above range, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of fast charge cycle can be reduced.
[0012] In some embodiments, 2.5≤P≤12. By adjusting the value of P within the above range, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of fast charge cycle can be reduced.
[0013] In some embodiments, the electrolyte contains fluoroethylene carbonate and 1,3-propane sultone, and based on the mass of the electrolyte, the mass percentage of fluoroethylene carbonate is A1%, the mass percentage of 1,3-propane sultone is A2%, and 2.5≤A1 / A2≤6. By making the electrolyte contain both fluoroethylene carbonate and 1,3-propane sultone and adjusting the value of A1 / A2 within the above range, the electrical conductivity between the first silicon-carbon particles and the second silicon-carbon particles can be improved, thereby further improving the thermal stability of the secondary battery after fast charge cycles and reducing the capacity loss of fast charge cycles.
[0014] In some embodiments, 3≤A1 / A2≤5. By adjusting the value of A1 / A2 within the above range, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of fast charge cycle can be reduced.
[0015] In some embodiments, 8≤A1≤18. By adjusting the value of A1 within the above range, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of fast charge cycle can be reduced.
[0016] In some embodiments, 1.5≤A2≤4. By adjusting the value of A2 within the above range, the thermal stability of the secondary battery after fast charge cycles can be further improved and the capacity loss of fast charge cycles can be reduced.
[0017] In some embodiments, the first silicon-carbon particles include silicon and carbon, and the mass proportion of silicon is C1%, 30≤C1≤50, based on the mass sum of the silicon and carbon elements of the first silicon-carbon particles; and / or, the second silicon-carbon particles include silicon and carbon, and the mass proportion of silicon is C2%, 40≤C2≤60, based on the mass sum of the silicon and carbon elements of the second silicon-carbon particles. By adjusting the values of C1 and / or C2 within the above range, the expansion degree of large-size silicon-carbon particles and small-size silicon-carbon particles during the fast charge cycle can be regulated, so that the small particles filled in the pores have an appropriate expansion degree, thereby maintaining the conductive network path inside the negative electrode material layer, and further reducing the stress unevenness caused by expansion, which can further improve the thermal stability of the secondary battery after the fast charge cycle and reduce the capacity loss of the fast charge cycle.
[0018] In some embodiments, 1.1≤C2 / C1≤1.5. By adjusting the value of C2 / C1 within the above range, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of fast charge cycle can be reduced.
[0019] In some embodiments, the electrolyte includes 2-methylbutyrate propyl, and the mass percentage of 2-methylbutyrate propyl is 0.01% to 0.1% based on the mass of the electrolyte. The electrolyte includes 2-methylbutyrate propyl and the mass percentage of 2-methylbutyrate propyl is adjusted within the above range, which can improve the conductivity of the solid electrolyte interface film on the surface of the second silicon-carbon particles, thereby further improving the thermal stability of the secondary battery after fast charge cycle and reducing the capacity loss of fast charge cycle.
[0020] In some embodiments, the electrolyte includes methylene methanedisulfonate, and the mass percentage of methylene methanedisulfonate is 0.1% to 0.8% based on the mass of the electrolyte. The electrolyte includes methylene methanedisulfonate and the mass percentage of methylene methanedisulfonate is adjusted within the above range to improve the toughness of the solid electrolyte interface film on the surface of the first silicon-carbon particles, thereby further improving the thermal stability of the secondary battery after fast charge cycles and reducing the capacity loss of fast charge cycles.
[0021] In some embodiments, the silicon-carbon particles include third silicon-carbon particles, and when 2<R<2.5, the silicon-carbon particles are third silicon-carbon particles; the number of the third silicon-carbon particles is N3, and N3 / (N1+N2+N3)<0.1. By making the negative electrode material layer include the third silicon-carbon particles and controlling the numbers of the third silicon-carbon particles, the first silicon-carbon particles, and the second silicon-carbon particles in the negative electrode material layer to meet the above relationship, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of the fast charge cycle can be reduced.
[0022] In some embodiments, the elongation of the negative electrode current collector is δ, 0.02≤δ≤0.08. By adjusting the elongation of the negative electrode current collector within the above range, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of fast charge cycle can be reduced.
[0023] In some embodiments, Denoted as M, the absolute value of M satisfies: |M|≤0.1. By adjusting the value of |M| within the above range, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of fast charge cycle can be reduced.
[0024] In some embodiments, the first silicon-carbon particles and the second silicon-carbon particles respectively include a carbon carrier and silicon grains at least partially distributed inside the carbon carrier, which can further improve the thermal stability of the secondary battery after fast charging cycles and reduce the capacity loss of fast charging cycles.
[0025] In a second aspect, the present application provides an electronic device, which includes the secondary battery provided in the first aspect of the present application. The electronic device provided in the second aspect of the present application achieves a higher energy density while further improving the thermal stability after the fast charge cycle and reducing the capacity loss of the fast charge cycle.
[0026] Additional aspects and advantages of the embodiments of the present application will be described, shown, or explained in part in the subsequent description through implementation of the embodiments of the present application. DETAILED DESCRIPTION
[0027] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.
[0028] Unless expressly stated otherwise, the following terms used in this application have the meanings indicated below.
[0029] In the first aspect, the present application provides a secondary battery. The secondary battery comprises a positive electrode, a negative electrode and an electrolyte, the negative electrode comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, the negative electrode material layer comprises silicon-carbon particles, and the particle size of the silicon-carbon particles is R µm. The silicon-carbon particles comprise first silicon-carbon particles and second silicon-carbon particles, when 2.5≤R≤13, the silicon-carbon particles are first silicon-carbon particles, and the number of particles of the first silicon-carbon particles is N1, when 0.1≤R≤2, the silicon-carbon particles are second silicon-carbon particles, and the number of particles of the second silicon-carbon particles is N2, and the negative electrode material layer satisfies: 5≤N2 / N1≤30. The secondary battery provided in the present application, while achieving a higher energy density, takes into account improving the thermal stability of the battery after a fast charge cycle and reducing the capacity loss rate of the fast charge cycle.
[0030] negative electrode
[0031] The negative electrode comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode material layer comprises a negative electrode active material. In some embodiments, the chargeable capacity of the negative electrode active material is greater than the discharge capacity of the positive electrode active material to prevent the active material (e.g., lithium metal) from being accidentally precipitated on the negative electrode during charging.
[0032] The negative electrode active material includes silicon carbon particles, the particle size of the silicon carbon particles is R μm, the silicon carbon particles include first silicon carbon particles and second silicon carbon particles, when 2.5≤R≤13, the silicon carbon particles are first silicon carbon particles, the number of particles of the first silicon carbon particles is N1, when 0.1≤R≤2, the silicon carbon particles are second silicon carbon particles, the number of particles of the second silicon carbon particles is N2, and the negative electrode material layer satisfies: 5≤N2 / N1≤30. In some embodiments, 5.1≤N2 / N1≤29.8. In some embodiments, 5.1≤N2 / N1≤24.6. In some embodiments, 10.3≤N2 / N1≤29.8. In some embodiments, 5.1≤N2 / N1≤10.3. In some embodiments, 10≤N2 / N1≤25. In some embodiments, 10.3≤N2 / N1≤24.6. In some embodiments, 24.6≤N2 / N1≤29.8. In some embodiments, 18.4≤N2 / N1≤22.2. In some embodiments, the value of N2 / N1 is 5, 5.8, 7.0, 8.9, 10.0, 10.6, 12.5, 13.4, 14.9, 16.5, 18.0, 18.4, 20.2, 20.8, 22.1, 24.2, 25.0, 26.1, 27.9, 29.3, 30 or a value in the range of any two thereof. By adjusting the value of N2 / N1 within the above range, the stacking state of silicon-carbon particles in the negative electrode material layer can be adjusted, and while achieving a higher energy density, the thermal stability of the secondary battery after fast charging cycle and the capacity loss of the fast charging cycle can be improved.
[0033] The number of silicon-carbon particles in the present application can be measured by methods known in the art, for example, a cross-sectional area of 40µm×80µm can be selected from the cross section of the negative electrode, and the selected cross-sectional area can be observed by a scanning electron microscope to count the number of first silicon-carbon particles and second silicon-carbon particles in the cross-sectional area. In some embodiments, within the area of 40µm×80µm, the number of first silicon-carbon particles is 2 to 19, and the number of second silicon-carbon particles is 51 to 199.
[0034] In some embodiments, the first silicon-carbon particles include silicon and carbon, and based on the mass sum of the silicon and carbon elements of the first silicon-carbon particles, the mass proportion of silicon is C1%, 30≤C1≤50. In some embodiments, 35≤C1≤48. In some embodiments, 31≤C1≤39. In some embodiments, 31≤C1≤35. In some embodiments, 35≤C1≤39. In some embodiments, 39≤C1≤48. In some embodiments, the value of C1 is 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50 or a value in the range of any two thereof. By adjusting the value of C1 within the above range, the thermal stability of the secondary battery after fast charging cycle can be further improved and the capacity loss of fast charging cycle can be reduced.
[0035] In some embodiments, the second silicon-carbon particles include silicon and carbon. Based on the sum of the masses of the silicon and carbon elements of the second silicon-carbon particles, the mass proportion of silicon is C2%, 40≤C2≤60. In some embodiments, 40≤C2≤52. In some embodiments, 52≤C2≤59. In some embodiments, the value of C2 is 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60 or a value within the range of any two thereof. By adjusting the value of C2 within the above range, the thermal stability of the secondary battery after fast charging cycle can be further improved and the capacity loss of the fast charging cycle can be reduced.
[0036] In some embodiments, 1.1≤C2 / C1≤1.5. In some embodiments, 1.1≤C2 / C1≤1.3. In some embodiments, 1.3≤C2 / C1≤1.5. In some embodiments, the value of C2 / C1 is 1.1, 1.2, 1.3, 1.4, 1.5 or a value in the range of any two thereof. By adjusting the value of C2 / C1 within the above range, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of fast charge cycle can be reduced.
[0037] In some embodiments, the silicon-carbon particles include third silicon-carbon particles, and when 2<R<2.5, the silicon-carbon particles are third silicon-carbon particles; the number of the third silicon-carbon particles is N3, and N3 / (N1+N2+N3)<0.1. In some embodiments, 0.01≤N3 / (N1+N2+N3)≤0.09. In some embodiments, the value of N3 / (N1+N2+N3) is 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09 or a value within the range of any two thereof. By making the negative electrode material layer include the third silicon-carbon particles and controlling the number of the third silicon-carbon particles, the first silicon-carbon particles and the second silicon-carbon particles to conform to the above relationship, the thermal stability of the secondary battery after fast charging cycle can be further improved and the capacity loss of the fast charging cycle can be reduced.
[0038] In the present application, the negative electrode current collector may include copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a polymer substrate coated with a conductive metal, etc. Among them, the conductive metal includes but is not limited to copper, nickel or titanium, and the material of the polymer substrate includes but is not limited to at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate or poly(p-phenylene terephthalamide). In the present application, there is no particular restriction on the thickness of the negative electrode current collector and the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4μm to 12μm, and the thickness of the single-sided negative electrode material layer is 20μm to 140μm. In the present application, the negative electrode material layer can be arranged on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of the negative electrode current collector or a partial area of the negative electrode current collector. There is no particular restriction in the present application, as long as the purpose of the present application can be achieved.
[0039] In some more preferred embodiments, the elongation of the negative electrode current collector is δ, 0.02≤δ≤0.08. In some embodiments, 0.02≤δ≤0.07. In some embodiments, 0.06≤δ≤0.08. In some embodiments, 0.02≤δ≤0.06. In some embodiments, 0.06≤δ≤0.07. In some embodiments, 0.07≤δ≤0.08. In some embodiments, the value of δ is 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08 or a value within the range of any two thereof. By adjusting the elongation of the negative electrode current collector within the above range, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of fast charge cycle can be reduced.
[0040] In some embodiments, Denoted as M, the absolute value of M satisfies: |M|≤0.1. In some embodiments, 0.01≤|M|≤0.1. In some embodiments, 0.01≤|M|≤0.07. In some embodiments, 0.03≤|M|≤0.1. In some embodiments, 0.01≤|M|≤0.05. In some embodiments, 0.03≤|M|≤0.07. In some embodiments, 0.05≤|M|≤0.1. In some embodiments, 0.01≤|M|≤0.03. In some embodiments, 0.03≤|M|≤0.05. In some embodiments, 0.05≤|M|≤0.07. In some embodiments, 0.07≤|M|≤0.1. In some embodiments, the value of |M| is 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, or a value in the range consisting of any two thereof. By adjusting the value of |M| within the above range, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of fast charge cycle can be reduced.
[0041] In some embodiments, the first silicon-carbon particles and the second silicon-carbon particles respectively include a carbon carrier and silicon grains at least partially distributed inside the carbon carrier, which can further improve the thermal stability of the secondary battery after fast charging cycles and reduce the capacity loss of fast charging cycles.
[0042] In some embodiments, the surface of the silicon-carbon particles may include a polymer, a conductive agent, a solid electrolyte, etc., separately or simultaneously, to further improve the performance of the secondary battery.
[0043] In some embodiments, the surface of the silicon-carbon particles may include a carbon layer, and the thickness of the carbon layer is preferably 10 to 100 nanometers. The carbon layer may be disposed on most of the surface of the silicon-carbon particles, and more preferably disposed on the entire surface of the silicon-carbon particles. By providing a carbon layer on the surface of the silicon-carbon particles, it is beneficial to reduce the gas production of the silicon-carbon particles during the preparation of the secondary battery, improve the flatness of the negative electrode sheet, and thus improve the performance of the secondary battery.
[0044] Optionally, the negative electrode material layer may further include crystalline carbon material and / or amorphous carbon material. The crystalline carbon material may be natural graphite, artificial graphite, etc., and the amorphous carbon may be soft carbon (low-temperature calcined carbon), hard carbon, intermediate phase pitch carbide or calcined coke, etc.
[0045] In some embodiments, the negative electrode material layer includes a conductive agent; the type of the conductive agent is not limited, and any known conductive material can be used. Examples of the conductive agent may include, but are not limited to, carbon black such as acetylene black and Super-P; amorphous carbon materials such as needle coke; carbon nanotubes; graphene, etc. The above conductive agents may be used alone or in any combination.
[0046] In the present application, the negative electrode material layer may further include a negative electrode binder. The negative electrode binder can improve the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. The type of negative electrode binder is not particularly limited, as long as it is a material that is stable to the solvent used in the electrolyte or electrode manufacturing. In some embodiments, the negative electrode binder includes a resin binder. Examples of resin binders include, but are not limited to, fluororesins, polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, and the like. When an aqueous solvent is used to prepare the negative electrode mixture slurry, the negative electrode binder includes, but is not limited to, hydroxyethylcarboxymethyl cellulose (HECMC) or its salt, carboxymethyl cellulose (CMC) or its salt, styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or its salt, polyacrylate, polyvinyl alcohol, and the like.
[0047] Illustratively, the negative electrode can be prepared by the following method: coating a negative electrode mixture slurry containing a negative electrode binder, silicon carbon particles, a conductive agent, etc. on a negative electrode current collector, drying it, and then rolling it to form a negative electrode material layer on both sides of the negative electrode current collector, thereby obtaining a negative electrode.
[0048] The present application has no particular restrictions on the compaction density of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the compaction density of the negative electrode sheet can be 1.0 g / cm 3 Up to 1.85 g / cm 3 The present application has no particular limitation on the cold pressing pressure of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the cold pressing pressure of the negative electrode sheet can be 3 tons to 30 tons.
[0049] Electrolyte
[0050] The electrolyte used in the secondary battery of the present application includes an electrolyte and a solvent for dissolving the electrolyte. In some embodiments, the electrolyte includes propylene carbonate and ethylene carbonate.
[0051] In some embodiments, based on the mass of the electrolyte, the mass percentage of ethylene carbonate is E%, and the mass percentage of propylene carbonate is P%, 2≤E / P≤8. In some embodiments, 2≤E / P≤6. In some embodiments, 2.5≤E / P≤8. In some embodiments, 2≤E / P≤4.5. In some embodiments, 2.5≤E / P≤6. In some embodiments, 4.5≤E / P≤8. In some embodiments, 2≤E / P≤2.5. In some embodiments, 2.5≤E / P≤4.5. In some embodiments, 4.5≤E / P≤6. In some embodiments, 6≤E / P≤8. In some embodiments, the value of E / P is 2, 2.4, 2.8, 3, 3.4, 3.6, 4.2, 4.3, 4.5, 5.1, 5.4, 5.5, 5.8, 6.3, 6.6, 6.8, 7.1, 7.6, 7.8, 8 or a value in the range composed of any two of these values. By adjusting the value of E / P within the above range, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of fast charge cycle can be reduced.
[0052] In some embodiments, 20≤E≤36. In some embodiments, 20≤E≤30. In some embodiments, 22≤E≤36. In some embodiments, 25≤E≤36. In some embodiments, 20≤E≤28. In some embodiments, 22≤E≤30. In some embodiments, 20≤E≤25. In some embodiments, 22≤E≤28. In some embodiments, 25≤E≤30. In some embodiments, 20≤E≤22. In some embodiments, 22≤E≤25. In some embodiments, 25≤E≤28. In some embodiments, 28≤E≤30. In some embodiments, 30≤E≤36. Exemplarily, the value of E is 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 35, 36 or a value in the range consisting of any two of these values. The present application regulates the above range of the value of E, which can further improve the thermal stability of the secondary battery after the fast charge cycle and reduce the capacity loss of the fast charge cycle.
[0053] In some embodiments, 2.5≤P≤12. In some embodiments, 2.5≤P≤10. In some embodiments, 5≤P≤12. In some embodiments, 2.5≤P≤8. In some embodiments, 5≤P≤10. In some embodiments, 8≤P≤12. In some embodiments, 2.5≤P≤5. In some embodiments, 5≤P≤8. In some embodiments, 8≤P≤10. In some embodiments, 10≤P≤12. Exemplarily, the value of P is 2.5, 3, 4, 5, 6, 7, 8, 10, 11, 12 or a value in the range consisting of any two of these values. The present application regulates the value of P in the above range, which can further improve the thermal stability of the secondary battery after fast charging cycle and reduce the capacity loss of fast charging cycle.
[0054] In some embodiments, the electrolyte includes fluoroethylene carbonate and 1,3-propane sultone, and based on the mass of the electrolyte, the mass percentage of fluoroethylene carbonate is A1%, the mass percentage of 1,3-propane sultone is A2%, and 2.5≤A1 / A2≤6. In some embodiments, 2.5≤A1 / A2≤5. In some embodiments, 3≤A1 / A2≤6. In some embodiments, 2.5≤A1 / A2≤4. In some embodiments, 3≤A1 / A2≤5. In some embodiments, 4≤A1 / A2≤6. In some embodiments, 2.5≤A1 / A2≤3. In some embodiments, 3≤A1 / A2≤4. In some embodiments, 4≤A1 / A2≤5. In some embodiments, 5≤A1 / A2≤6. In some embodiments, the value of A1 / A2 is 2.5, 2.6, 2.8, 3.0, 3.1, 3.3, 3.6, 3.8, 3.9, 4.1, 4.3, 4.5, 4.7, 4.8, 4.9, 5.1, 5.4, 5.6, 5.7, 5.9, 6 or a value in the range of any two thereof. By making the electrolyte contain fluoroethylene carbonate and 1,3-propane sultone at the same time and adjusting the value of A1 / A2 within the above range, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of fast charge cycle can be reduced.
[0055] In some embodiments, 8≤A1≤18. In some embodiments, 8≤A1≤15. 10≤A1≤18. In some embodiments, 8≤A1≤12. In some embodiments, 10≤A1≤15. In some embodiments, 10.5≤A1≤18. In some embodiments, 8≤A1≤10.5. In some embodiments, 10≤A1≤12. In some embodiments, 10.5≤A1≤15. In some embodiments, 12≤A1≤18. In some embodiments, 8≤A1≤10. In some embodiments, 10≤A1≤10.5. In some embodiments, 10.5≤A1≤12. In some embodiments, 12≤A1≤15. In some embodiments, 15≤A1≤18. In some embodiments, the value of A1 is 8, 8.5, 8.9, 9.4, 9.6, 10.6, 10.7, 11.5, 12.2, 12.4, 13.2, 13.4, 14.0, 14.5, 15.1, 15.8, 16.4, 16.5, 17.2, 17.5, 18 or a value in the range of any two thereof. In some embodiments, by adjusting the value of A1 within the above range, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of fast charge cycle can be reduced.
[0056] In some embodiments, 1.5≤A2≤4. In some embodiments, 1.5≤A2≤3.5. In some embodiments, 3≤A2≤4. In some embodiments, 1.5≤A2≤3. In some embodiments, 3≤A2≤3.5. In some embodiments, 3.5≤A2≤4. In some embodiments, the value of A2 is 1.5, 1.6, 1.8, 2.0, 2.1, 2.3, 2.4, 2.5, 2.7, 2.8, 2.9, 3.0, 3.2, 3.3, 3.5, 3.6, 3.7, 3.8, 4 or a value within the range of any two thereof. By adjusting the value of A2 within the above range, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of fast charge cycle can be reduced.
[0057] In some embodiments, the electrolyte includes 2-methylbutyric acid propyl ester, and the mass percentage of 2-methylbutyric acid propyl ester is 0.01% to 0.1% based on the mass of the electrolyte. In some embodiments, the mass percentage of 2-methylbutyric acid propyl ester is 0.01% to 0.05%. In some embodiments, the mass percentage of 2-methylbutyric acid propyl ester is 0.05% to 0.1%. In some embodiments, the mass percentage of 2-methylbutyric acid propyl ester is 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1% or a value within the range of any two thereof. By making the electrolyte include 2-methylbutyric acid propyl ester and adjusting the mass percentage of 2-methylbutyric acid propyl ester within the above range, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of fast charge cycle can be reduced.
[0058] In some embodiments, the electrolyte includes methylene methanedisulfonate, and the mass percentage of methylene methanedisulfonate is 0.1% to 0.8% based on the mass of the electrolyte. In some embodiments, the mass percentage of methylene methanedisulfonate is 0.1% to 0.5%. In some embodiments, the mass percentage of methylene methanedisulfonate is 0.5% to 0.8%. In some embodiments, the mass percentage of methylene methanedisulfonate is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8% or a value within the range of any two thereof. By making the electrolyte include methylene methanedisulfonate and adjusting the mass percentage of methylene methanedisulfonate within the above range, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of the fast charge cycle can be reduced.
[0059] The present application has no particular restrictions on the types of other components of the electrolyte, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl ethyl carbonate, butylene carbonate, vinyl ethylene carbonate, methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanoic acid, valerolactone or caprolactone, ethylene dimethacrylate, butylene carbonate, ethyl acetate, methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanoic acid, valerolactone or caprolactone, ethylene dimethacrylate At least one of alcohol dimethyl ether, dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate.
[0060] In some embodiments, the electrolyte is not particularly limited, and any substance known as an electrolyte can be used. The weight of the electrolyte is not particularly limited as long as the effects of the present application are not impaired.
[0061] positive electrode
[0062] The positive electrode includes a positive electrode collector and a positive electrode material layer disposed on a surface of the positive electrode collector.
[0063] The positive electrode material layer contains positive electrode active material, and the positive electrode material layer can be one layer or multiple layers. Each layer of the multiple layers of positive electrode active material can contain the same or different positive electrode active materials. The positive electrode active material is any material that can reversibly embed and de-embed alkali metal ions.
[0064] The positive electrode active material includes a lithium transition metal oxide containing nickel and other transition metals. In the lithium transition metal oxide including nickel and other transition metals, the amount of nickel relative to the total molar number of the transition metal may be 60 mol% or more, for example, 75 mol% or more, for example, 80 mol% or more, for example, 85 mol% or more, or for example, 90 mol% or more.
[0065] For example, the lithium transition metal oxide may be a compound represented by the following formula α:
[0066] Formula α: Li a Ni x Co y M z O 2-b A b ,
[0067] Wherein, in formula α, 0.9≤a≤1.2, 0≤b≤0.2, 0.6≤x<1, 0<y≤0.3, 0<z≤0.3, and x+y+z=1, M is at least one selected from manganese (Mn), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al) or boron (B), and A is F, S, Cl, Br or a combination thereof. For example, the above subscripts may be 0.7≤x<1, 0<y≤0.3, and 0<z≤0.3; 0.8≤x<1, 0<y≤0.3, and 0<z≤0.3; 0.8≤x<1, 0<y≤0.2, and 0<z≤0.2; 0.83≤x<0.97, 0<y≤0.15, and 0<z≤0.15; or 0.85≤x<0.95, 0<y≤0.1, and 0<z≤0.1.
[0068] For example, the lithium transition metal oxide may be at least one compound represented by the following formula β or formula γ:
[0069] Formula β: LiNi x Co y Mn z O2,
[0070] Wherein, in formula β, 0.6≤x≤0.95, 0<y≤0.2, and 0<z≤0.1, for example, 0.7≤x≤0.95, 0<y≤0.3, and 0<z≤0.3.
[0071] Formula γ: LiNi x Co y Al z O2,
[0072] Wherein, in formula γ, 0.6≤x≤0.95, 0<y≤0.2, and 0<z≤0.1, for example, 0.7≤x≤0.95, 0<y≤0.3, and 0<z≤0.3, for example, 0.8≤x≤0.95, 0<y≤0.3, and 0<z≤0.3, for example, 0.82≤x≤0.95, 0<y≤0.15, and 0<z≤0.15, for example, 0.85≤x≤0.95, 0<y≤0.1, and 0<z≤0.1.
[0073] For example, the lithium transition metal oxide may be LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.88 Co 0.08 Mn 0.04 O2、LiNi 0.8 Co 0.15 Mn 0.05 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.88 Co 0.1 Mn 0.02 O2、LiNi 0.8 Co 0.15 Al 0.05 O2 or LiNi 0.88 Co 0.1 Al 0.02 O2.
[0074] According to another embodiment, the positive electrode active material includes at least one active material selected from the group consisting of Li-Ni-Co-Al (NCA), Li-Ni-Co-Mn (NCM), lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMnO2), lithium nickel oxide (LiNiO2) and lithium iron phosphate (LiFePO4).
[0075] In some embodiments, the positive electrode material layer includes a positive electrode conductive material; the type of the positive electrode conductive material is not limited, and any known conductive material can be used. Examples of positive electrode conductive materials may include, but are not limited to, carbon black such as acetylene black and Super-P; amorphous carbon materials such as needle coke; carbon nanotubes; graphene, etc. The above positive electrode conductive materials may be used alone or in any combination.
[0076] There is no particular restriction on the type of positive electrode binder used in the manufacture of the positive electrode material layer. In the case of a coating method, any material that can be dissolved or dispersed in the liquid medium used in the manufacture of the electrode can be used. Examples of positive electrode binders may include, but are not limited to, one or more of the following: resin polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose; rubber polymers such as styrene-butadiene rubber (SBR), nitrile rubber (NBR), fluororubber, isoprene rubber, polybutadiene rubber, and ethylene-propylene rubber; styrene-butadiene-styrene block copolymers or their hydrogenates, ethylene-propylene-diene terpolymers (EPDM), Thermoplastic elastomer polymers such as styrene·ethylene·butadiene·ethylene copolymers, styrene·isoprene·styrene block copolymers or their hydrogenated products; soft resin polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene·vinyl acetate copolymers, propylene·α-olefin copolymers; fluorine-based polymers such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene, fluorinated polyvinylidene fluoride, polytetrafluoroethylene·ethylene copolymers; polymer compositions having ion conductivity of alkali metal ions (especially lithium ions), etc. The above positive electrode binders can be used alone or in any combination.
[0077] There is no limitation on the type of solvent used to form the positive electrode slurry, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the conductive material, the positive electrode binder, and the thickener used as needed. Examples of solvents used to form the positive electrode slurry may include any of aqueous solvents and organic solvents. Examples of aqueous media may include, but are not limited to, a mixed medium of alcohol and water or water, etc. Examples of organic media may include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran (THF); amides such as N-methylpyrrolidone (NMP), dimethylformamide, and dimethylacetamide; aprotic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide, etc.
[0078] Thickeners are generally used to adjust the viscosity of the slurry. In the case of using an aqueous medium, the thickener and styrene-butadiene rubber (SBR) emulsion can be used for slurrying. The type of thickener is not particularly limited, and examples thereof may include, but are not limited to, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof. The above thickeners may be used alone or in any combination.
[0079] The type of positive electrode current collector is not particularly limited, and it can be any material known to be suitable for use as a positive electrode current collector. Examples of positive electrode current collectors may include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and materials such as carbon cloth and carbon paper. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.
[0080] In order to reduce the electronic contact resistance between the positive electrode current collector and the positive electrode material layer, the surface of the positive electrode current collector may include a conductive additive or a conductive coating. Examples of conductive additives may include, but are not limited to, carbon and precious metals such as gold, platinum, and silver. Examples of conductive coatings may include a mixture layer containing an inorganic oxide, a conductive agent, and a binder.
[0081] The positive electrode can be made by forming a positive electrode material layer containing a positive electrode active material and a binder on a current collector. The manufacture of a positive electrode using a positive electrode active material can be carried out by a conventional method, that is, the positive electrode active material and the binder, as well as the conductive material and the thickener as required, are dry-mixed to form a sheet, and the obtained sheet is pressed onto the positive electrode current collector; or these materials are dissolved or dispersed in a liquid medium to form a slurry, and the slurry is applied to the positive electrode current collector and dried to form a positive electrode material layer on the current collector, thereby obtaining a positive electrode.
[0082] Isolation film
[0083] In order to prevent short circuit, a separator is usually provided between the positive electrode and the negative electrode. In this case, the electrolyte of the present application is usually used by infiltrating the separator.
[0084] There is no particular restriction on the material and shape of the isolation membrane, as long as the effect of the present application is not significantly impaired. The isolation membrane may be a resin, glass fiber, inorganic substance, etc. formed of a material that is stable to the electrolyte of the present application. In some embodiments, the isolation membrane includes a porous sheet or a non-woven fabric-like material with excellent liquid retention. Examples of materials for resin or glass fiber isolation membranes may include, but are not limited to, polyolefins, aromatic polyamides, polytetrafluoroethylene, polyether sulfone, etc. In some embodiments, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The materials of the above isolation membranes may be used alone or in any combination.
[0085] The separator may also be a material formed by laminating the above materials, examples of which include, but are not limited to, a three-layer separator formed by laminating polypropylene, polyethylene, and polypropylene in this order.
[0086] Examples of inorganic materials may include, but are not limited to, oxides such as aluminum oxide and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates (eg, barium sulfate, calcium sulfate, etc.). The form of the inorganic material may include, but is not limited to, granular or fibrous.
[0087] The separator may be in the form of a thin film, examples of which include, but are not limited to, nonwoven fabrics, woven fabrics, microporous films, etc. In the thin film form, the separator has a pore size of 0.01 μm to 1 μm and a thickness of 5 μm to 50 μm. In addition to the above-mentioned independent thin film separators, the following separators can also be used: a separator formed by forming a composite porous layer containing the above-mentioned inorganic particles on the surface of the positive electrode and / or the negative electrode using a resin-based adhesive, for example, a separator formed by using a fluororesin as an adhesive to form a porous layer on both sides of the positive electrode with alumina particles having a particle size of 90% less than 1 μm.
[0088] The thickness of the separator is arbitrary. In some embodiments, the thickness of the separator is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the separator is less than 50 μm, less than 40 μm, or less than 30 μm. When the thickness of the separator is within the above range, insulation and mechanical strength can be ensured, and the energy density of the secondary battery can be ensured.
[0089] The present application further provides an electronic device, which includes the secondary battery of the present application.
[0090] The purpose of the secondary battery of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. In some embodiments, the secondary battery of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.
[0091] Example
[0092] Below, taking lithium-ion batteries as an example, examples and comparative examples are given to explain the implementation of the secondary battery of the present application in more detail. Those skilled in the art will understand that the preparation method described in this application is only an example, and any other suitable preparation method is within the scope of this application. Various tests and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "parts" and "%" are mass references.
[0093] Test Method
[0094] Thermal stability after fast charge cycles
[0095] (1) At 25℃±1℃, charge the lithium-ion battery at a constant current of 4.0C to 4.35V, then charge at a constant voltage of 4.35V until the current drops to 0.05C, and then discharge the lithium-ion battery at a constant current of 1.0C to 3.0V before stopping. This is considered a charge and discharge cycle. Perform 200 charge and discharge cycles on the lithium-ion battery.
[0096] (2) Place the lithium-ion battery in a hot box and heat it from 25°C to 150°C at a heating rate of 5°C / min. After reaching 150°C, maintain the temperature and start timing. After maintaining the temperature for 1 hour, observe the state of the lithium-ion battery. The lithium-ion battery is considered to have passed the test if there is no smoke, fire, or explosion. Each group of examples tests 10 lithium-ion batteries. "1 / 10" means that one of the 10 lithium-ion batteries passed the test.
[0097] Capacity loss rate of fast charge cycle
[0098] (1) At 25℃±1℃, charge the lithium-ion battery at a constant current of 0.5C to 4.35V, then charge it at a constant voltage of 4.35V to 0.025C, let it stand for 5 minutes, and then discharge it at a constant current of 0.5C to 3.0V. Record the discharge capacity Q1 of the lithium-ion battery.
[0099] (2) At 25℃±1℃, charge the lithium-ion battery at a constant current of 4.0C to 4.35V, then charge at a constant voltage of 4.35V until the current drops to 0.05C, and then discharge the lithium-ion battery at a constant current of 1.0C to 3.0V before stopping. This is considered a charge and discharge cycle. Perform 300 charge and discharge cycles on the lithium-ion battery.
[0100] (3) At 25℃±1℃, charge the lithium-ion battery at a constant current of 0.5C to 4.35V, then charge it at a constant voltage of 4.35V to 0.025C, let it stand for 5 minutes, and then discharge it at a constant current of 0.5C to 3.0V, and record the discharge capacity Q2 of the lithium-ion battery. The capacity loss rate after fast charge cycle is (Q1-Q2) / Q1×100%.
[0101] Particle size and number of particles (Rµm, N1、 N2 and N3)
[0102] The tested battery was disassembled to obtain the negative electrode, which was cut into a size of 1 cm×1 cm. The cut surface of the negative electrode was then polished using argon plasma polishing technology to obtain a negative electrode cross-section sample.
[0103] The negative electrode cross section was observed in the backscattered mode of the scanning electron microscope. A 40µm×80µm area to be tested was randomly selected from the negative electrode cross section. The cross-sectional area of all silicon-carbon particles in the area to be tested was counted and recorded as S. According to S=(π×R 2 ) / 4 formula to calculate the particle size R of the selected silicon-carbon particles. The silicon-carbon particles with a particle size greater than or equal to 2.5µm and less than or equal to 13µm are the first silicon-carbon particles, the silicon-carbon particles with a particle size R greater than or equal to 0.1µm and less than or equal to 2µm are the second silicon-carbon particles, and the silicon-carbon particles with a particle size greater than 2µm and less than 2.5µm are the third silicon-carbon particles.
[0104] The number of the first silicon-carbon particles is N1, the number of the second silicon-carbon particles is N2, and the number of the third silicon-carbon particles is N3.
[0105] Silicon mass percentage test (C1% and C2%)
[0106] The negative electrode was cut into a size of 1 cm×1 cm, and then the cut surface of the negative electrode was polished using an argon plasma polishing technique to obtain a negative electrode cross-section sample.
[0107] The negative electrode cross-section sample was observed in the backscattered mode of a scanning electron microscope, and three first silicon-carbon particles and three second silicon-carbon particles were randomly selected from the negative electrode cross-section sample. The weight percentage of silicon and carbon in the selected particles was tested by energy dispersive X-ray analysis, and the mass percentage of silicon in each particle was calculated. The arithmetic average of the mass percentage of silicon in the first silicon-carbon particles or the second silicon-carbon particles was calculated, and the mass percentage of silicon was C1% and C2%.
[0108] Elongation test of negative electrode current collector (δ)
[0109] Disassemble the tested battery to obtain the negative electrode, remove the negative electrode material layer to obtain the negative electrode current collector. Cut the negative electrode current collector into a test sample with a length × width of 200mm × 15mm, and mark the original gauge length L0 on the test sample. At a test temperature of 25℃±1℃, use a universal material testing machine to stretch the negative electrode current collector along the length direction at a stretching rate of 5mm / min. The elongation of the test sample at break is L1mm, and the elongation of the negative electrode current collector δ=L1 / L0.
[0110] Example 1-1
[0111] <Preparation of negative electrode>
[0112] Preparation of silicon carbon particles:
[0113] The carbon skeleton material was ball-milled and then classified by a jet classifier. The average particle size of the first carbon skeleton material was 8.9 µm, and the average particle size of the second carbon skeleton material was 1.2 µm.
[0114] The first carbon skeleton material was placed in a rotary furnace, heated to 600°C in an argon atmosphere and kept warm for one hour, and then the atmosphere was switched to a mixture of argon and silane (the volume ratio of silane to argon was 2:8), and vapor deposition was performed at a deposition temperature of 500°C for 6.5 hours to obtain the first silicon-carbon particles.
[0115] The second carbon skeleton material is placed in a rotary furnace, heated to 480°C in an argon atmosphere and kept warm for one hour, and then the atmosphere is switched to a mixture of argon and silane (the volume ratio of silane to argon is 2:8), and vapor deposition is performed at a deposition temperature of 600°C for 3.5 hours to obtain second silicon-carbon particles.
[0116] A carbon layer is formed on the surface of the first silicon-carbon particle and the second silicon-carbon particle by chemical vapor deposition. The thickness of the carbon layer can be controlled by controlling the time of chemical vapor deposition. The average thickness of the carbon layer on the surface of the first silicon-carbon material is 36 nm, and the average thickness of the carbon layer on the surface of the second silicon-carbon particle is 13 nm.
[0117] Preparation of negative electrode sheet:
[0118] The first silicon-carbon particles with a carbon layer on the surface, the second silicon-carbon particles with a carbon layer on the surface and artificial graphite are mixed uniformly in a mass ratio of 9.8:0.2:90 as negative electrode active materials. The mixed negative electrode active material, styrene-butadiene rubber, polyacrylic acid, carbon nanotubes and carboxymethyl cellulose are mixed in a mass ratio of 95.8:2.4:0.5:0.5:0.8, and then deionized water is added as a solvent and stirred uniformly to prepare a negative electrode slurry with a solid content of 45wt%. The negative electrode slurry is uniformly coated on one surface of the negative electrode current collector copper foil and dried to obtain a negative electrode sheet coated with a negative electrode material layer on one side. The above steps are repeated on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet coated with a negative electrode material layer on both sides. After cold pressing, cutting, slitting and drying, a negative electrode sheet is obtained.
[0119] <Preparation of positive electrode>
[0120] Lithium cobalt oxide, conductive carbon black, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 95:2:3, and N-methylpyrrolidone (NMP) is added. The mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 70wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 9μm, and dried to obtain a positive electrode sheet coated with a positive electrode material layer on one side. Repeat the above steps on the other surface of the positive electrode current collector aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. After cold pressing, cutting, slitting, and drying, a positive electrode sheet is obtained.
[0121] <Preparation of Electrolyte>
[0122] In a dry argon atmosphere glove box, lithium hexafluorophosphate (LiPF6) and 1,3-propane sultone were dissolved in a mixed solution containing propyl propionate, ethyl propionate, ethylene carbonate, propylene carbonate, and fluoroethylene carbonate. Based on the mass of the electrolyte, the mass percentage of LiPF6 was 12.5%, the mass percentage of ethylene carbonate was 28%, the mass percentage of propylene carbonate was 8.5%, the mass percentage of fluoroethylene carbonate was 12%, and the mass percentage of 1,3-propane sultone was 3%. The remainder was propyl propionate and ethyl propionate, and the mass percentage ratio of propyl propionate to ethyl propionate was 1:1.
[0123] <Diaphragm>
[0124] A porous polyethylene film with a thickness of 15 μm was used as the separator.
[0125] <Preparation of lithium-ion batteries>
[0126] The positive electrode and negative electrode prepared as above are connected to the pole ears respectively. They are stacked via a separator to obtain a laminate. Then, the laminate is housed in an aluminum laminate housing together with an electrolyte. The opening of the housing is heat-sealed, and a lithium-ion battery is prepared through steps such as formation and degassing.
[0127] Examples 1-2 to 1-14, Comparative Examples 1 and 2
[0128] Except for adjusting the parameters according to Table 1, the rest is the same as Example 1-1. When preparing the negative electrode slurry, the addition amount of the first silicon-carbon particles, the second silicon-carbon particles and the artificial graphite is adjusted so that the number N1 of the first silicon-carbon particles, the number N2 of the second silicon-carbon particles and N2 / N1 are as shown in Table 1. When preparing the silicon-carbon particles, the duration of the vapor deposition is adjusted so that the silicon element ratio C1 of the first silicon-carbon particles and the silicon element ratio C2 of the second silicon-carbon particles are as shown in Table 1.
[0129] Table 1
[0130]
[0131] As can be seen from Table 1, the present application controls the silicon-carbon particles in the negative electrode material layer to include the first silicon-carbon particles and the second silicon-carbon particles. By adjusting the particle number of the first silicon-carbon particles and the second silicon-carbon particles to meet 5.1≤N2 / N1≤29.8, it is possible to achieve a higher energy density while taking into account improving the thermal stability of the secondary battery after the fast charge cycle and reducing the capacity loss rate of the fast charge cycle. In particular, when the particle number of the two satisfies 10.3≤N2 / N1≤24.6, it is possible to further improve the thermal stability of the secondary battery after the fast charge cycle and reduce the capacity loss rate of the fast charge cycle.
[0132] In particular, when the mass ratio of silicon in the first silicon-carbon particles and the second silicon-carbon particles is respectively adjusted to meet 31≤C1≤48 and 40≤C2≤59, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss rate of the fast charge cycle can be reduced. In particular, when the mass ratio of silicon in the first silicon-carbon particles and the second silicon-carbon particles meets 1.1≤C2 / C1≤1.5, the thermal stability of the secondary battery after fast charge cycle can be more significantly improved and the capacity loss rate of the fast charge cycle can be reduced.
[0133] Example 2-1 to Example 2-18
[0134] Except for adjusting the parameters according to Table 2, the rest is the same as Example 1-2. When the parameters shown in Table 2 increase compared with Example 1-2, the content of propyl propionate and ethyl propionate decreases accordingly; when the parameters shown in Table 2 decrease compared with Example 1-2, the content of propyl propionate and ethyl propionate increases accordingly, and the mass percentage ratio of propyl propionate and ethyl propionate remains unchanged. "\" indicates that the electrolyte does not contain the substance.
[0135] Table 2
[0136]
[0137] It can be seen from Table 2 that, on the basis of the negative electrode system of the present application, by regulating the mass content of ethylene carbonate and propylene carbonate in the electrolyte to satisfy the relationship: 2≤E / P≤8, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of the fast charge cycle can be reduced. In particular, when the mass content of the two satisfies 2.5≤E / P≤6, the secondary battery can achieve better thermal stability after fast charge cycle and reduce the capacity loss rate. Among them, when the mass content of ethylene carbonate in the electrolyte is regulated to satisfy 20≤E≤36, and / or when the mass content of propylene carbonate in the electrolyte is regulated to satisfy 2.5≤P≤12, it is beneficial to further improve the thermal stability of the secondary battery after fast charge cycle and reduce the capacity loss of the fast charge cycle.
[0138] In particular, when the mass percentage of fluoroethylene carbonate and 1,3-propane sultone contained in the electrolyte is regulated to meet 2.5≤A1 / A2≤6, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of the fast charge cycle can be reduced. In particular, the mass percentage of the two satisfies 3≤A1 / A2≤5, which can further improve the thermal stability of the secondary battery after fast charge cycle and reduce the capacity loss of the fast charge cycle. Among them, when the mass percentage of fluoroethylene carbonate and 1,3-propane sultone is respectively regulated to meet 8≤A1≤18 and / or 1.5≤A2≤4, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of the fast charge cycle can be reduced.
[0139] In particular, regulating the electrolyte to include 2-methylbutyric acid propyl ester and adjusting the mass percentage of 2-methylbutyric acid propyl ester within the above range can further improve the thermal stability of the secondary battery after fast charge cycles and reduce the capacity loss of fast charge cycles. In particular, regulating the electrolyte to include methylene methanedisulfonate and adjusting the mass percentage of methylene methanedisulfonate within the above range can further improve the thermal stability of the secondary battery after fast charge cycles and reduce the capacity loss of fast charge cycles.
[0140] Example 3-1 to Example 3-6
[0141] Except for adjusting the parameters according to Table 3, the rest is the same as Example 1-2. When preparing the negative electrode slurry, the addition amount of the first silicon-carbon particles, the second silicon-carbon particles and the artificial graphite is adjusted so that the number of the first silicon-carbon particles and the number of the second silicon-carbon particles are as shown in Table 3. The elongation δ of the negative electrode current collector is adjusted in the process of preparing the negative electrode current collector so that the elongation δ of the negative electrode current collector is as shown in Table 3.
[0142] Table 3
[0143]
[0144] In Table 3, M= .
[0145] It can be seen from Table 3 that when the elongation δ of the negative electrode current collector is adjusted to meet 0.02≤δ≤0.08, the thermal stability of the secondary battery after fast charge cycle can be further improved and the capacity loss of the fast charge cycle can be reduced. On this basis, when M satisfies |M|≤0.1, the thermal stability of the secondary battery after fast charge cycle can be more significantly improved and the capacity loss of the fast charge cycle can be reduced.
[0146] The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the principles of the present application should be included in the protection scope of the present application.
Claims
1. A secondary battery comprising a positive electrode, a negative electrode and an electrolyte, wherein: The negative electrode comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode material layer comprises silicon carbon particles, and the particle size of the silicon carbon particles is R μm; The silicon-carbon particles include first silicon-carbon particles and second silicon-carbon particles; when 2.5≤R≤13, the silicon-carbon particles are first silicon-carbon particles, and the number of the first silicon-carbon particles is N1; when 0.1≤R≤2, the silicon-carbon particles are second silicon-carbon particles, and the number of the second silicon-carbon particles is N2; 5.1≤N2 / N1≤29.8; The elongation of the negative electrode current collector is δ, 0.02≤δ≤0.
08. 2 . The secondary battery according to claim 1 , wherein 10≤N2 / N1≤25. 3 . The secondary battery according to claim 1 , wherein the electrolyte comprises ethylene carbonate and propylene carbonate, and based on the mass of the electrolyte, the mass percentage of the ethylene carbonate is E%, and the mass percentage of the propylene carbonate is P%, and 2≤E / P≤8.
4. The secondary battery according to claim 3, which satisfies at least one of the following: (1)20≤E≤36; (2)2.5≤P≤12; (3) 2.5≤E / P≤6.
5. The secondary battery according to claim 1, wherein the electrolyte comprises fluoroethylene carbonate and 1,3-propane sultone, and based on the mass of the electrolyte, the mass percentage of the fluoroethylene carbonate is A1%, the mass percentage of the 1,3-propane sultone is A2%, and 2.5≤A1 / A2≤6.
6. The secondary battery according to claim 5, which satisfies at least one of the following: (1)8≤A1≤18; (2)1.5≤A2≤4; (3)3≤A1 / A2≤5.
7. The secondary battery according to any one of claims 1 to 6, wherein the first silicon-carbon particles contain silicon and carbon, and based on the sum of the mass of the silicon and carbon elements of the first silicon-carbon particles, the mass proportion of the silicon element is C1%, 30≤C1≤50; and / or, The second silicon-carbon particles contain silicon and carbon. Based on the sum of the masses of the silicon and carbon elements of the second silicon-carbon particles, the mass proportion of the silicon element is C2%, 40≤C2≤60.
8. The secondary battery according to claim 7, 1.1≤C2 / C1≤1.
5.
9. The secondary battery according to any one of claims 1 to 6, wherein the electrolyte satisfies at least one of the following conditions: (1) The electrolyte contains 2-methylbutyric acid propyl ester, and the mass percentage of the 2-methylbutyric acid propyl ester is 0.01% to 0.1% based on the mass of the electrolyte; (2) The electrolyte contains methylene methanedisulfonate, and the mass percentage of the methylene methanedisulfonate is 0.1% to 0.8% based on the mass of the electrolyte.
10. The secondary battery according to claim 1, wherein the silicon-carbon particles include third silicon-carbon particles; when 2<R<2.5, the silicon-carbon particles are third silicon-carbon particles; The number of the third silicon-carbon particles is N3, and N3 / (N1+N2+N3) is less than 0.
1.
11. The secondary battery according to claim 1, Denoted as M, the absolute value of M satisfies: |M|≤0.
1. 12 . The secondary battery according to claim 1 , wherein the first silicon-carbon particles and the second silicon-carbon particles both comprise a carbon carrier and silicon crystals at least partially distributed inside the carbon carrier. 13 . An electronic device comprising the secondary battery according to claim 1 .
Citation Information
Patent Citations
Non-aqueous electrolyte and lithium secondary battery using same
CN103597648A
Electrolytic solution and secondary battery
CN106410279A
Quick-charge type lithium ion battery and preparation method thereof
CN116315036A
Secondary battery and electronic device
CN118156416A
Negative pole piece as well as preparation method and application thereof
CN118198270A